Genetic transformation in oilseed brassicas - A review - RANI, TEENA; YADAV, RAM C; YADAV, NEELAM R; RANI, ASHA; SINGH, DHIRAJ (The Indian Journal of Agricultural Sciences, 2026)
Brassica is the most economically important genus in the cruciferae family, remarkable for containing agricultural and horticultural crops than any other genus. It includes over 30 wild species, their cultivars and hybrids including six most important species of Brassicas, Brassica campestris, B. juncea, B. carinata and B. napus which are oil yielding species. Due to their agricultural importance, Brassicas have been the subject of much scientific interest and considerable progress has been made in Brassica biotechnology. The molecular breeding and transformation technology for the introduction of desirable traits are two main strategies for its improvement. Several genes of agronomic importance have been identified in Brassica species and other identified genes have been transferred in Brassica species. Plant regeneration, transformation methods and gene of interest are the main requirements for gene transfer in any crop. Regeneration has been optimized via organogenesis and somatic embryogenesis using various explants. Transformation systems have been developed in almost all the economically important species of Brassica such as B. juncea, B. napus, B. rapa, B. oleracea, B. nigra, and B. carinata. Transformation has improved Brassica species for many traits, such as herbicide resistance, insect resistance, salt tolerance, oil quality improvement, for the production of pharmacological and industrial products, development of male-sterile lines and restoration system. Among different methods of transformation, Agrobacterium mediated genetic transformation is most widely used for Brassica and it is generally quite efficient and practical for most species in the genus. However, there is still a need for development of efficient transformation methods to overcome genotype dependency. In the present paper, the work on regeneration and genetic transformation in the Brassica species will be reviewed.